DIRECTIVE ILLOCUTIONARY ACTS OF JAMES CORDEN’S UTTERANCES “THE HOST” - Wulan Angelia Sembiring; Ambalegin Ambalegin (Asosiasi Ide Bahasa Kepri, 2022)
This descriptive qualitative research explored one of speech acts phenomena. The researchers took directive acts types as the object of this research. Utterances of directive acts that the host produced were used as the data source. The directive acts types were analyzed by employing Searle and Vanderveken (1985)’s theory regarding types of directive acts. Observational method was adopted to analyze data and it also used non-participatory technique collection. The data were analyzed through pragmatic identity method and competence in equalizing technique by Sudaryanto (2015). It discovered that there had 18 utterances of directive acts in James Corden’s utterances. There were eight of command, six of request, prohibition and question had two data. The type of permission was not uttered by the host and guests. The dominant type was command because the host was the host, which means he owned higher degree compared to the guests.